Teamwork and Individual Behavior in Optimizing Performance in Cooperative Institutions in Developing Country Provinces - Fitriani, Putri Dwi; Syafirah, Raudya; Febriadha, Zetta Bethrien; Suzana, Anna (Green Publisher Indonesia, 2024)
This study aims to identify the relationship between teamwork and the performance of the cooperative facilitator, identify the relationship between individual behavior and the performance of the cooperative facilitator, and explore how teamwork and individual behavior can simultaneously affect the performance of the cooperative facilitator itself. Researchers use descriptive quantitative methods and collect data obtained through measuring instruments in the form of questionnaires. The research sample used from this study was 50 cooperative facilitators who became respondents based on the characteristics of respondents who had the highest level of Facilitators, and could conduct training for Facilitators at the level below and had certification as BNSP Cooperative Facilitators. Based on the results of statistical tests, there is an influence of the work team and the performance of cooperative facilitators of 0.406 with t-statistc values of 2.221 > 1.96 and P values of 0.026 < 0.050, Based on statistical tests of individual behavior on the performance of cooperative facilitators of 0.436 and t-statistc of 2.054. > 1.96 and with a P value of 0.040 < 0.050. Based on the R-Square value of these three variables, it is stated that the Independent Variables of Work Team and Individual Behavior in this study affect the dependent variable Performance by 0.659 or 65.9% so that it can be said that the coefficient of Performance in this study is said to be moderate.